Dietary Tryptophan Induces Opposite Health-Related Responses in the Senegalese Sole (Solea senegalensis) Reared at Low or High Stocking Densities With Implications in Disease Resistance - Azeredo, Rita; Machado, Marina; Martos-Sitcha, Juan A.; Martínez-Rodríguez, Gonzalo; Moura, Joana; Peres, Helena; Oliva-Teles, Aires; Afonso, António; Mancera, Juan M.; Costas, Benjamín (Frontiers in Physiology, 2019)
High rearing densities are typical conditions of both inland and onshore intensive aquaculture units. Despite obvious drawbacks, this strategy is nonetheless used to increase production profits. Such conditions inflict stress on fish, reducing their ability to cope with disease, bringing producers to adopt therapeutic strategies. In an attempt to overcome deleterious effects of chronic stress, Senegalese sole, Solea senegalensis, held at low (LD) or high density (HD) were fed tryptophan-supplemented diets with final tryptophan content at two (TRP2) or four times (TRP4) the requirement level, as well as a control and non-supplemented diet (CTRL) for 38 days. Fish were sampled at the end of the feeding trial for evaluation of their immune status, and mortalities were recorded following intra-peritoneal infection with Photobacterium damselae subsp. piscicida. Blood was collected for analysis of the hematological profile and innate immune parameters in plasma. Pituitary and hypothalamus were sampled for the assessment of neuro-endocrine-related gene expression. During the feeding trial, fish fed TRP4 and held at LD conditions presented higher mortalities, whereas fish kept at HD seemed to benefit from this dietary treatment, as disease resistance increased over that of CTRL-fed fish. In accordance, cortisol level tended to be higher in fish fed both supplemented diets at LD compared to fish fed CTRL, but was lower in fish fed TRP4 than in those fed TRP2 under HD condition. Together with lower mRNA levels of proopiomelanocortin observed with both supplementation levels, these results suggest that higher levels of tryptophan might counteract stress-induced cortisol production, thereby rendering fish better prepared to cope with disease. Data regarding sole immune status showed no clear effects of tryptophan on leucocyte numbers, but TRP4-fed fish displayed inhibited alternative complement activity (ACH50) when held at LD, as opposed to their HD counterparts whose ACH50 was higher than that of CTRL-fed fish. In conclusion, while dietary tryptophan supplementation might have harmful effects in control fish, it might prove to be a promising strategy to overcome chronic stress-induced disease susceptibility in farmed Senegalese sole.